Gaming hospital-level pneumonia 30-day mortality and readmission measures by legitimate changes to diagnostic coding - Sjoding, Michael W. (Crit Care Med, 2015)
OBJECTIVE: Risk-standardized 30-day mortality and hospital readmission rates for pneumonia are increasingly being tied to hospital reimbursement to incentivize the delivery of high quality care. Such measures may be susceptible to gaming by recoding patients with pneumonia to a primary diagnosis of sepsis or respiratory failure. We sought to determine the degree to which hospitals can game mortality or readmission measures and change their rankings by recoding patients with pneumonia. DESIGN AND SETTING: Simulated experimental study of 2,906 US acute care hospitals with at least 25 admissions for pneumonia using 2009 Medicare data. PARTICIPANTS: Elderly (age ≥ 65 years) Medicare fee-for-service beneficiaries hospitalized with pneumonia. Patients eligible for recoding to sepsis or respiratory failure were those with a principal ICD-9-CM discharge code for pneumonia and secondary codes for respiratory failure or acute organ dysfunction. INTERVENTIONS: None MEASUREMENTS AND MAIN RESULTS: We measured the number of hospitals that improved their pneumonia mortality or readmission rates after recoding eligible patients. When a sample of 100 hospitals with pneumonia mortality rates above the 50(th) percentile recoded all eligible patients to sepsis or respiratory failure, 90 hospitals (95% CI: 84 - 95) improved their mortality rate (mean improvement 1.09%, 95% CI: 0.94 – 1.28%) and 41 hospitals dropped below the 50(th) percentile (95% CI: 33 - 52). When a sample of 100 hospitals with pneumonia readmission rates above the 50(th) percentile recoded all eligible patients, 66 hospitals (95% CI: 54 - 75) improved their readmission rate (mean improvement 0.34%, 95% CI: 0.19 – 0.45%) and 15 hospitals (95% CI: 9 - 22) dropped below the 50(th) percentile. CONCLUSIONS: Hospitals can improve apparent pneumonia mortality and readmission rates by recoding pneumonia patients. CMS should consider changes to their methods used to calculate hospital-level pneumonia outcome measures to make them less susceptible to gaming.